THE INFLUENCE OF LEADERSHIP STYLE, MOTIVATION AND COMPENSATION ON WORK DISCIPLINE AND PERFORMANCE OF REGIONAL PUBLIC COMPANIES EMPLOYEES - I Gede Putu Kawiana; Syamsulbahri Syamsulbahri; Ratnawita Ratnawita; Achmad Barlian; Musran Munizu (Jurnal Scientia, 2023)
In terms of income or costs, good human resource management will optimize firm performance. The purpose of this research is to examine the impact of leadership style, salary, incentive, and punishment on employee performance. This is a quantitative qualitative study using data collected via questionnaires and analyzed using SEM-PLS via the SmartPLS. The sample approach utilized in this study was nonprobability sampling with a total sampling method, namely 40 workers of Perumda marketing division. The findings revealed that directly, leadership style and salary had no significant influence on work discipline, however motivation did. Then, directly, leadership style and motivation have no influence on employee performance, however salary and work discipline have an effect on employee performance. Then, leadership style and salary have no influence on employee performance via work discipline, however motivation has an effect on employee performance through work discipline.